The Influence of Family Wealth and Parent Education Level on Students Reading Literacy - Abu Nawas (Deputy of Social Sciences and Humanities, the Indonesia Institute of Sciences (LIPI), 2019)
This study aims to examine the influence of family background factors in terms of family wealth and parent education levels on students reading performance in Indonesia. The study utilises secondary data from the OECDs Programme for International Student Assessment (PISA) 2015 for Indonesia, in which 6513 students participated. This also specifically highlights the analysis of family wealth and parent education levels in possibly predicting the students reading literacy in Indonesia. In analysing the data, a quantitative approach was used which utilised statistically different analysis such as t-test, one-way ANOVA, two-way ANOVA, correlation and multiple linear regression analysis using WesVar version 5.1 software.The result found there were significant different reading scores between students from different family wealth and parent education levels. The students from high family wealth performed better than they with middle and low wealthy. Likewise, the children with highly educated mother and father had high scores than students whose parents had low and did not complete primary school. Moreover, the result of correlation and regression analysis revealed that all predictor variables, WEALTH, MISCED and FISCED, significantly associate and predict better reading literacy performance of 15-year-old students in Indonesia for PISA 2015 survey. Therefore, the implications of the study highlight opportunities to reform educational policies through data and evidence.